Hip and knee arthroplasty - patient's experiences of pain and rehabilitation after discharge from hospital. (November 2017) - Sjøveian, Aud Karin Hjelpdahl; Leegaard, Marit
Abstract: Background: Fast-track clinical pathways for hip and knee arthroplasty is being implemented in several western countries. The treatment entails patient involvement, optimal pain management, intensive mobilization and early discharge. Limited research has been carried out on patient's experiences after discharge. Purpose: The purpose of the study is to describe how patients experience pain and manage the rehabilitation process the first six weeks after discharge. Method: The study followed a qualitative descriptive design. Semi-structured interviews were conducted with 12 participants three months after discharge from hip or knee arthroplasty. Findings: Patients experienced varying degrees of pain the first three to five weeks after discharge. Walking-training and sleep were affected by pain or stiffness in joints and muscles, and several needed help from family members to perform activities of daily living (ADL). Several participants would have like more individualized information about pain and exercises before discharge. Some experienced that the municipal care services failed to follow up on issues related to pain. Conclusion: The study illuminates that patients may need more individualized and adapted information prior to discharge, as well as more multidisciplinary follow-up by doctors, physiotherapists and possibly home care nurses. We recommend more studies examining how patients experience pain and rehabilitation during the first weeks after completing arthroplasty.